2015
DOI: 10.17554/j.issn.2224-3992.2015.03.495-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Variceal Haemorrhage

Abstract: One of the most important complications of portal hypertension, in the setting of liver cirrhosis or of non-cirrhotic portal hypertension, is upper gastrointestinal bleeding from ruptured gastroesophageal varices and portal hypertensive gastropathy. The management of the acute variceal bleeding is a multidisciplinary process that includes the initial assessment of the patient, effective resuscitation, timely diagnosis, control of bleeding and prevention of early rebleeding and complications such as infection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 97 publications
1
1
0
Order By: Relevance
“…We found that patients categorized as CPS-B formed the highest percentage (44%), followed by CPS-A and CPS-C, in agreement with Thajeel et al [10], who reported the highest percentage of their pediatric study group as CPS-B (49%) in contrast to 32% and 19% as CPS-A and C, and in the study of Maher et al [12] groups A, B and C comprised 26.7%, 50% and 23.3%, respectively. According to upper endoscopic findings, 40% of patients were classified as group I (patients had EVs) and 60% as group II (patients had no EVs), which was generally in agreement with Dell'Era et al [13] and Hanquinet et al [14], who documented that EVs were found in about 50% and 54% of their pediatric population. Also D' Amico et al [15] and Garcia-Tsao et al [16] reported similar results but in adult patients with CLD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that patients categorized as CPS-B formed the highest percentage (44%), followed by CPS-A and CPS-C, in agreement with Thajeel et al [10], who reported the highest percentage of their pediatric study group as CPS-B (49%) in contrast to 32% and 19% as CPS-A and C, and in the study of Maher et al [12] groups A, B and C comprised 26.7%, 50% and 23.3%, respectively. According to upper endoscopic findings, 40% of patients were classified as group I (patients had EVs) and 60% as group II (patients had no EVs), which was generally in agreement with Dell'Era et al [13] and Hanquinet et al [14], who documented that EVs were found in about 50% and 54% of their pediatric population. Also D' Amico et al [15] and Garcia-Tsao et al [16] reported similar results but in adult patients with CLD.…”
Section: Discussionsupporting
confidence: 86%
“…According to upper endoscopic findings, 40% of patients were classified as group I (patients had EVs) and 60% as group II (patients had no EVs), which was generally in agreement with Dell’Era et al . [ 13 ] and Hanquinet et al . [ 14 ], who documented that EVs were found in about 50% and 54% of their pediatric population.…”
Section: Discussionmentioning
confidence: 99%